The alkaloids of Tinomiscium philippinense diels - Milan, Rosita Serafico 1940-
A crystalline base I, m.p. 220(degrees C), was isolated from the stem bark of Tinomiscium philippinense Diels. Methylation of this tertiary phenolic base I, C20 H23 O4 N, with diazomethane yielded white crystals, C21 H25 O4 N, m.p. 140(degrees C). Due to the very small yield of base I (.003%), physical methods were mostly used in the elucidation of its structure. Mixed melting point determination, elemental analysis and UV, IR, NMR and mass spectral determinations clearly established the identity of base I and its methylated base to be tetrahydrocolumbamine and tetrahydropalmatine, respectively.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1967.
Keywords: Alkaloids